Tunable nanocarrier morphologies from glycopolypeptide-based amphiphilic biocompatible star copolymers and their carbohydrate specific intracellular delivery - Pati, Debasis; Das, Soumen; Patil, Naganath G.; Parekh, Nimisha; Anjum, Dalaver H.; Dhaware, Vinita; Ambade, Ashootosh V.; Sen Gupta, Sayam (Biomacromolecules, 2016)
Nanocarriers with carbohydrates on the surface represent a very interesting class of drug-delivery vehicles because carbohydrates are involved in biomolecular recognition events in vivo. We have synthesized biocompatible miktoarm star copolymers comprising glycopolypeptide and poly(e-caprolactone) chains using ring-opening polymerization and ``click chemistry''. The amphiphilic copolymers were self-assembled in water into morphologies such as nanorods, polymersomes, and micelles with carbohydrates displayed on the surface. We demonstrate that the formation of nanostructure could be tuned by chain length of the blocks and was not affected by the type of sugar residue. These nanostructures were characterized in detail using a variety of techniques such as TEM, AFM, cryogenic electron microscopy, spectrally resolved fluorescence imaging, and dye encapsulation techniques. We show that it is possible to sequester both hydrophobic as well as hydrophilic dyes within the nanostructures. Finally, we show that these noncytotoxic mannosylated rods and polymersomes were selectively and efficiently taken up by MDA-MB-231 breast cancer cells, demonstrating their potential as nanocarriers for drug delivery.